Administration of Lactobacillus reuteri Combined with Clostridium butyricum Attenuates Cisplatin-Induced Renal Damage by Gut Microbiota Reconstitution, Increasing Butyric Acid Production, and Suppressing Renal Inflammation - Hsiao, Yu-Ping; Chen, Hsiao-Ling; Tsai, Jen-Ning; Lin, Meei-Yn; Liao, Jiunn-Wang; Wei, Meng-Syuan; Ko, Jiunn-Liang; Ou, Chu-Chyn (Nutrients, 2021)
Cisplatin-induced nephrotoxicity is associated with gut microbiota disturbance. The present study aimed to investigate whether supplementation of Lactobacillus reuteri and Clostridium butyricum (LCs) had a protective effect on cisplatin-induced nephrotoxicity through reconstruction of gut microbiota. Wistar rats were given different treatments: control, cisplatin (Cis), cisplatin + C. butyricum and L. reuteri (Cis+LCs), and C. butyricum and L. reuteri (LCs). We observed that cisplatin-treated rats supplemented with LCs exhibited significantly decreased renal inflammation (KIM-1, F4/80, and MPO), oxidative stress, fibrosis (collagen IV, fibronectin, and a-SMA), apoptosis, concentration of blood endotoxin and indoxyl sulfate, and increased fecal butyric acid production compared with those without supplementation. In addition, LCs improved the cisplatin-induced microbiome dysbiosis by maintaining a healthy gut microbiota structure and diversity; depleting Escherichia-Shigella and the Enterobacteriaceae family; and enriching probiotic Bifidobacterium, Ruminococcaceae, Ruminiclostridium_9, and Oscillibacter. Moreover, the LCs intervention alleviated the cisplatin-induced intestinal epithelial barrier impairment. This study indicated LCs probiotic serves as a mediator of the gut–kidney axis in cisplatin-induced nephrotoxicity to restore the intestinal microbiota composition, thereby suppressing uremic toxin production and enhancing butyrate production. Furthermore, the renoprotective effect of LCs is partially mediated by increasing the anti-inflammatory effects and maintaining the integrity of the intestinal barrier.